Tahapan Pemberdayaan Berbasis Aset Komunitas pada Desa Wisata Pentingsari Yogyakarta - Putri Noer Aini; Sri Dewi Wulandari (Mahesa Research Center, 2021)
One of the efforts to reduce poverty is through community asset-based empowerment, as has been done by the people of Pentingsari Village, Yogyakarta. Through the Pentingsari Tourism Village program, people who initially relied on income only from agriculture can now be more prosperous through village nature-based tourism management and the social life of village communities. Various development obstacles can be overcome by carrying out development stages. Therefore, the focus of this study is to determine the stages of asset-based empowerment carried out by the people of Pentingsari Village in 2008 - 2018. This study uses a literature study approach. Empowerment in Pentingsari Village shows a relevance to Christopher Dureau's asset-based empowerment theory. In this study, the findings of community asset-based development in Pentingsari Village from 2008-2018 include the six stages of empowerment. The implementation of these six stages has always involved the local community and has brought positive changes to the community. The implementation of the stage of studying and arranging scenarios (define), the stage of uncovering the past (discovery), and the stage of dreaming of the future are carried out continuously, with the role of the pioneer character being more dominant. After that, the asset mapping stage was carried out in a sustainable and sustainable manner, with the asset mobilization stage and the monitoring stage through routine forums attended by community members and village officials.